2007
DOI: 10.1017/s0007114507842292
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of studies of iodine intake and recommendations for number of samples in groups and in individuals

Abstract: The iodine intake level in a population is determined in cross-sectional studies. Urinary iodine varies considerably and the reliability of studies of iodine nutrition and the number of samples needed is unsettled. We performed a longitudinal study of sixteen healthy men living in an area of mild to moderate iodine deficiency. Iodine and creatinine concentrations were measured in spot urine samples collected monthly for 13 months. From these data we calculated the number of urine samples needed to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
191
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(212 citation statements)
references
References 23 publications
14
191
0
2
Order By: Relevance
“…For studies that relied on one-time spot samples (all but this study and ref 27), there is also the problem of large temporal variability for the same individual (27). Recently Andersen et al (47) concluded that estimating population iodine excretion requires 100-500 urine samples and for an individual, g12 urine samples are needed to obtain ( 20% accuracy. If this applied to milk, only the present data and the data set in ref 28 will qualify.…”
Section: (47)mentioning
confidence: 95%
“…For studies that relied on one-time spot samples (all but this study and ref 27), there is also the problem of large temporal variability for the same individual (27). Recently Andersen et al (47) concluded that estimating population iodine excretion requires 100-500 urine samples and for an individual, g12 urine samples are needed to obtain ( 20% accuracy. If this applied to milk, only the present data and the data set in ref 28 will qualify.…”
Section: (47)mentioning
confidence: 95%
“…In 1052 participants of this subgroup, the iodine concentration was measured in fasting morning urine samples in 2006. Serum TSH and FT 4 were measured twice with an interval of 4 years (2002 and 2006). The mean interval between the measurements was 4.1 years (range 2.8-5.4 years).…”
Section: Subjectsmentioning
confidence: 99%
“…To assess the iodine status of a population, the median iodine concentration of series of single urine samples is the most widely used measurement (1,3). In large population studies, there is a leveling out of the dayto-day variation, and the median value of the urinary iodine concentration in samples can be used to assess whether a population is iodine sufficient (4). According to the World Health Organization (WHO) criteria, a population has an optimal iodine intake if its median urine iodine concentration is between 100 and 199 mg/l and no more than 20% of the population has an urinary iodine concentration of 50 mg/l or less (1,3).…”
Section: Introductionmentioning
confidence: 99%
“…Iodine supplementation resulted in an expected increase in median morning ioduria, as well as an increase in the percentage of patients with desirable urinary iodine concentration above 150 μg/L to 61.1%. We realise that the number of participants in our study is not adequate to assess iodine sufficiency in the population [11]; however, the increase in iodine urinary excretion confirms additional iodine intake in the "thyroxine + iodine" group. In healthy pregnant women fT4 concentrations decrease at the second and third trimester [12].…”
Section: Rycina 1 Zmiany Stężeń Jodu W Moczu Porannym Oraz Tsh Ft4 mentioning
confidence: 69%